Global trait–environment relationships of plant communities. Issue 12 (December 2018) - Bruelheide, Helge; Dengler, Jürgen; Purschke, Oliver; Lenoir, Jonathan; Jiménez-Alfaro, Borja; Hennekens, Stephan; Botta-Dukát, Zoltán; Chytrý, Milan; Field, Richard; Jansen, Florian; Kattge, Jens; Pillar, Valério; et al.
Abstract Plant functional traits directly affect ecosystem functions. At the species level, trait combinations depend on trade-offs representing different ecological strategies, but at the community level trait combinations are expected to be decoupled from these trade-offs because different strategies can facilitate co-existence within communities. A key question is to what extent community-level trait composition is globally filtered and how well it is related to global versus local environmental drivers. Here, we perform a global, plot-level analysis of trait–environment relationships, using a database with more than 1.1 million vegetation plots and 26, 632 plant species with trait information. Although we found a strong filtering of 17 functional traits, similar climate and soil conditions support communities differing greatly in mean trait values. The two main community trait axes that capture half of the global trait variation (plant stature and resource acquisitiveness) reflect the trade-offs at the species level but are weakly associated with climate and soil conditions at the global scale. Similarly, within-plot trait variation does not vary systematically with macro-environment. Our results indicate that, at fine spatial grain, macro-environmental drivers are much less important for functional trait composition than has been assumed from floristic analyses restricted to co-occurrence in large grid cells. Instead, trait combinations seem to be predominantly filtered by local-scale factors such as disturbance, fine-scale soil conditions, niche partitioning and biotic interactions. Although plant functional trait combinations reflect ecological trade-offs at the species level, little is known about how this translates to whole communities. Here, the authors show that global trait composition is captured by two main dimensions that are only weakly related to macro-environmental drivers.